2018
DOI: 10.21082/jbio.v12n2.2016.p119-130
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication to Reveal Adaptation Clue of Plant to Environmental Stress: A Case Study of NBS-LRR Genes in Soybean

Abstract: ABSTRAK Gen responsif terhadap cekaman lingkungan yang bertahan setelah mengalami duplikasi genom skala kecil merupakan bagian dari duplikasi genom. Namun demikian, informasi duplikasi gen yang berpengaruh terhadap sifat adaptif tanaman terhadap perubahan lingkungan masih terbatas. Ulasan ini menyajikan gambaran peristiwa duplikasi dalam genom tanaman yang berdampak terhadap duplikasi gen yang berkaitan dengan perubahan lingkungan, informasi duplikasi gen yang merupakan bagian dari mekanisme adaptasi, kasus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Among the resistance genes in plants that have been cloned and characterized, 61% of them belong to NBS-LRR gene (Shao et al, 2016;Kourelis and van der Hoorn, 2018;Xing et al, 2018). The accumulation of mutations in the NBS-LRR gene can increase the complexity of the NBS-LRR gene clusters and can generate new resistance types by recombining or rearranging with each other, such as gene duplication, unequal exchange, chromosomal abnormal recombination, gene conversion (Michelmore and Meyers, 1998;Meyers et al, 2003;Nagy and Bennetzen, 2008;Marone et al, 2013;Lestari et al, 2017;Lv et al, 2017). The resistance mechanism in the NBS-LRR gene cluster region is complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the resistance genes in plants that have been cloned and characterized, 61% of them belong to NBS-LRR gene (Shao et al, 2016;Kourelis and van der Hoorn, 2018;Xing et al, 2018). The accumulation of mutations in the NBS-LRR gene can increase the complexity of the NBS-LRR gene clusters and can generate new resistance types by recombining or rearranging with each other, such as gene duplication, unequal exchange, chromosomal abnormal recombination, gene conversion (Michelmore and Meyers, 1998;Meyers et al, 2003;Nagy and Bennetzen, 2008;Marone et al, 2013;Lestari et al, 2017;Lv et al, 2017). The resistance mechanism in the NBS-LRR gene cluster region is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…In the cloning and functional study of the wheat powdery mildew resistance gene Pm60, it was found that the NBS-LRR powdery mildew resistance gene can interact with its adjacent NBS-LRR structural gene to jointly provide resistance against powdery mildew (Zou et al, 2018). The diversity of Rps genes on soybean chromosome 3 may be caused by the translocation, recombination or rearrangement of functional NBS-LRR genes in the NBS-LRR gene cluster to lead the different resistance types to P. sojae (Kang et al, 2012;Lestari et al, 2017). It requires further experimental support to explore whether there is a large sequence change in the mapping interval of RpsYD25 compared with the reference genome Williams82 such as the presence of other genes.…”
Section: Discussionmentioning
confidence: 99%